2017
DOI: 10.1016/j.cmet.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 Is a Sugar-Induced Hormone Associated with Sweet Intake and Preference in Humans

Abstract: The liking and selective ingestion of palatable foods-including sweets-is biologically controlled, and dysfunction of this regulation may promote unhealthy eating, obesity, and disease. The hepatokine fibroblast growth factor 21 (FGF21) reduces sweet consumption in rodents and primates, whereas knockout of Fgf21 increases sugar consumption in mice. To investigate the relevance of these findings in humans, we genotyped variants in the FGF21 locus in participants from the Danish Inter99 cohort (n = 6,514) and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
178
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 178 publications
(202 citation statements)
references
References 65 publications
23
178
0
1
Order By: Relevance
“…These findings are consistent with data from animal studies showing that FGF21 signals to reward centres in the brain [1,2]. The human genetic studies found no detectable effect on the risk of type 2 diabetes and only nominal evidence for an effect on BMI [13].…”
Section: Introductionsupporting
confidence: 81%
See 4 more Smart Citations
“…These findings are consistent with data from animal studies showing that FGF21 signals to reward centres in the brain [1,2]. The human genetic studies found no detectable effect on the risk of type 2 diabetes and only nominal evidence for an effect on BMI [13].…”
Section: Introductionsupporting
confidence: 81%
“…These findings are consistent with data from animal studies showing that FGF21 signals to reward centres in the brain [1,2]. The human genetic studies found no detectable effect on the risk of type 2 diabetes and only nominal evidence for an effect on BMI [13].Here we aimed to extend the characterisation of the phenotypes associated with the variant in FGF21 using 451,000 individuals from the UK Biobank. We reasoned that genotype-phenotype associations of FGF21 would inform developers of FGF21 based therapies as to their potential beneficial and adverse effects.…”
supporting
confidence: 72%
See 3 more Smart Citations